Slow recovery from disturbance: a 20 year study of Ascophyllum canopy clearances - Ingólfsson, A.; Hawkins, S.J. (Journal of the Marine Biological Association of the United Kingdom, 2008)
We describe an experiment where Ascophyllym nodosum was removed from two 1 x 1 m plots in south-western Iceland in August 1985. The plots were studied regularly until 2005. Recovery of the Ascophyllum canopy took 7–8 years. The understorey algae in one of the plots consisted mostly of extensive growth of Cladophora rupestris, which died within a year of Ascophyllum clearance. No Cladophora had reappeared by 2005, although it was healthy and abundant in control plots throughout the study period. Thus even after 20 years the community had not recovered from disturbance.